2013
DOI: 10.1212/wnl.0b013e31828cf7e1
|View full text |Cite
|
Sign up to set email alerts
|

PRRT2 mutation correlated with phenotype of paroxysmal kinesigenic dyskinesia and drug response

Abstract: The Bruno et al. 1 criteria are commonly used to diagnose paroxysmal kinesigenic dyskinesia (PKD), listed as follows:• Identified kinesigenic trigger for the attacks • Short duration of attacks (1 minute) • No loss of consciousness or pain during attacks • Exclusion of other organic diseases and normal neurologic examination • Control of attacks with phenytoin or carbamazepine, if tried • Age at onset between 1 and 20 years, if no family history of PKD Our previous study has identified PRRT2 as a causative gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 8 publications
7
35
1
Order By: Relevance
“…These findings correspond well with a previous study that found no difference between these two groups, with the exception of premonitory sensation 16. However, another study found a higher prevalence of the choreoathetotic phenotype and longer duration of paroxysmal dyskinesia in PKD patients with PRRT2 gene mutations 17. In the present study, there was no significant difference between the two groups, even when the duration of episodes was dichotomized into <5 s and >5 s ( p =0.580) just like the previous study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings correspond well with a previous study that found no difference between these two groups, with the exception of premonitory sensation 16. However, another study found a higher prevalence of the choreoathetotic phenotype and longer duration of paroxysmal dyskinesia in PKD patients with PRRT2 gene mutations 17. In the present study, there was no significant difference between the two groups, even when the duration of episodes was dichotomized into <5 s and >5 s ( p =0.580) just like the previous study.…”
Section: Discussionsupporting
confidence: 92%
“…Echoing previous studies,16,17 PKD patients with PRRT2 gene mutations were younger at disease onset in the present study. Assessment of the clinical data revealed that the clinical features of paroxysmal movement were highly typical and homogeneous, similar to previous studies 12,18.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…5,8,9 Of note, PRRT2 gene mutations have also been identified in other paroxysmal disorders such as benign familial infantile seizures (BFIS), paroxysmal nonkinesigenic dyskinesia, paroxysmal exercise-induced dyskinesia, hemiplegic migraine, paroxysmal torticollis, episodic ataxia, childhood absence epilepsy, and febrile seizures. 18 Considering the remarkable pleiotropy of the PRRT2 gene with the still-expanding clinical spectrum and the limited researches into the genotype-phenotype analysis of PKD, [19][20][21][22] we analyzed the clinical manifestations and genetic features of our patients with PKD and conducted the genotype-phenotype correlation analysis. 18 Considering the remarkable pleiotropy of the PRRT2 gene with the still-expanding clinical spectrum and the limited researches into the genotype-phenotype analysis of PKD, [19][20][21][22] we analyzed the clinical manifestations and genetic features of our patients with PKD and conducted the genotype-phenotype correlation analysis.…”
mentioning
confidence: 99%
“…Often, a dramatic improvement is seen with anticonvulsant treatment (sodium channel blockers) (particularly in PRRT2 mutation carriers 8 ), making this a possible way to confirm the diagnosis. 3 The overall prognosis of PKD is good as the frequency of attacks tends to decline with age and spontaneous remission occurs in a subset of patients.…”
Section: 3mentioning
confidence: 99%